Red blood cell folate and benign prostatic hyperplasia: results from the NHANES 2001-2008 - TingTing Chen; YuanPeng Huang (The Aging Male)
Background Benign prostatic hyperplasia (BPH) affects 30% of men worldwide, folate is essential for life. However, few studies have investigated the relationship between folate levels and BPH. The present study aims to explore the relationship between red blood cell (RBC) folate, a better indicator of long-term folate intake, and BPH in United States (US) men.Methods We used statistics from four cycles of the “National Health and Nutrition Examination Survey” (NHANES2001-2008), RBC folate data come from laboratory data and BPH date come from questionnaire data. A multivariate conditional logistic regression model and subgroup analysis were using to assess the association between RBC folate and BPH.Results 647 males from four survey cycles in the NHANES2001-2008, of which, 574 men (88.7%) had BPH. After adjusting for potential confounders, a considerable correlation was observed between RBC folate and BPH; With the first quintiles of RBC folate as the reference, multivariable-adjusted odds ratios (ORs) and confidence intervals (95% CIs) of the second, third, fourth, and the highest quintiles were 1.19 (0.58 ∼ 2.44), 1.39 (0.65 ∼ 2.97), 2.27 (0.96 ∼ 5.39), 2.26 (1.35 ∼ 3.76) and 5.37 (1.85 ∼ 15.59), respectively.Conclusions Individuals with high levels of RBC folate were associated with an increased risk of self-reported benign prostatic hyperplasia of US men.